PENERAPAN SOSIALISASI VISI DAN MISI KOPERASI DALAM PENGUATAN TATA KELOLA DAN ARAH STRATEGIS UMKM SKALA KECIL - Aziza, Maleeka Noor; Zhafira, Nayla (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
Small-scale Micro, Small, and Medium Enterprises (MSMEs) often operate without a clear strategic direction and structured governance, resulting in reactive decision-making and limited business sustainability.Cooperatives, as collective economic institutions, play a strategic role in strengthening MSME managerial capacity through the internalization of organizational values, vision, and mission. This study aims to analyze the implementation of cooperative vision and mission socialization in strengthening governance and strategic direction of small-scale MSMEs. The research employs a descriptive qualitative approach through socialization sessions, participatory workshops, decision-making simulations, and action plan development. The findings indicate improvements in MSMEs' understanding of business objectives, consistency in decision-making, and ability to formulate measurable strategic plans. The study concludes that the socialization of cooperative vision and mission functions not merely as value dissemination but as an effective instrument for strengthening governance and strategic orientation of small-scale MSMEs.Keywords : cooperative, vision and mission, governance, strategic direction, MSMEs